2018
DOI: 10.1007/jhep06(2018)129
|View full text |Cite
|
Sign up to set email alerts
|

The all-loop conjecture for integrands of reggeon amplitudes in $$ \mathcal{N}=4 $$ SYM

Abstract: In this paper we present the all-loop conjecture for integrands of Wilson line form factors, also known as reggeon amplitudes, in N = 4 SYM. In particular we present a new gluing operation in momentum twistor space used to obtain reggeon tree-level amplitudes and loop integrands starting from corresponding expressions for on-shell amplitudes. The introduced gluing procedure is used to derive the BCFW recursions both for tree-level reggeon amplitudes and their loop integrands. In addition we provide predictions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 79 publications
(190 reference statements)
0
5
0
Order By: Relevance
“…2 Form factors of a variety of operators have been calculated in N = 4 sYM theory using modern techniques originally developed in the context of scattering amplitudes. These include recursion relations [14][15][16][17], on-shell diagrams, polytopes and Graßmannians [18][19][20][21][22][23], twistor space actions [24][25][26][27], a connected prescription [28][29][30], color-kinematics duality [31][32][33], and a dual description via the AdS/CFT correspondence [14,[34][35][36][37][38]. These results are currently limited to two loops for n ≥ 3.…”
Section: Jhep04(2021)147mentioning
confidence: 99%
“…2 Form factors of a variety of operators have been calculated in N = 4 sYM theory using modern techniques originally developed in the context of scattering amplitudes. These include recursion relations [14][15][16][17], on-shell diagrams, polytopes and Graßmannians [18][19][20][21][22][23], twistor space actions [24][25][26][27], a connected prescription [28][29][30], color-kinematics duality [31][32][33], and a dual description via the AdS/CFT correspondence [14,[34][35][36][37][38]. These results are currently limited to two loops for n ≥ 3.…”
Section: Jhep04(2021)147mentioning
confidence: 99%
“…Bootstrap methods have also proved to be successful for form factors: the symbol bootstrap method has been applied to form factors at two loops [23] and recently at much higher loops in [31] with the help of the form factor operator product expansion (OPE) [32,33]; besides, a new bootstrap strategy based on the master-integral ansatz has been developed to compute a two-loop four-point form factor in [34]. See also some other studies in [35][36][37][38][39][40][41][42][43]. A recent introduction and review of form factors in N = 4 SYM can be found in [44].…”
Section: Introductionmentioning
confidence: 99%
“…2 Form factors of a variety of operators have been calculated in N = 4 sYM theory using modern techniques originally developed in the context of scattering amplitudes. These include recursion relations [14][15][16][17], on-shell diagrams, polytopes and Graßmannians [18][19][20][21][22][23], twistor space actions [24][25][26][27], a connected prescription [28][29][30], color-kinematics duality [31][32][33], and a dual description via the AdS/CFT correspondence [14,[34][35][36][37][38]. These results are currently limited to two loops for n ≥ 3.…”
Section: Introductionmentioning
confidence: 99%